Fetal Nucleic Acids in Maternal Circulation: A Genetic Resource for Noninvasive Prenatal Diagnosis. (20th September 2012) - Banerjee, Monisha; Misra, Deepika
Abstract : Invasive prenatal diagnosis (PND) holds a multitude of psychological considerations for women, their partners, family and community as a whole. Earlier, the non-invasive screening methods for certain disorders were serum analytes or ultrasound with low sensitivity and high false positivity. The discovery of fetal DNA in maternal plasma has opened up an approach for noninvasive PND (NIPD). Presence of fetal cells and cell-free fetal DNA (cffDNA) in the blood of pregnant women has been accepted universally and constant efforts are being made to enrich fetal DNA from maternal blood/plasma. Real-time quantitative polymerase chain reaction (qrt-PCR) has enabled fetal DNA to serve as a marker for chromosomal abnormalities, for example, trisomy 21, preterm labor, and preeclampsia. In India, PND is provided in few centers since invasive methods require trained gynecologists, this limits investigation and therefore NIPD with cffDNA from mother's blood will revolutionize fetal medicine. The present paper deals with the latest developments in procurement of cffDNA, the probable source and enrichment of fetal DNA in maternal plasma, and the current status of its detection methodologies, applications, and its potential to be used as a powerful diagnostic tool.